Technological characteristics of glauconite rocks in Bakchar deposit (Western Siberia); MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Rudmin M. A. Maksim Andreevich; Mazurov A. K. Aleksey Karpovich; Makarov B. I.; Reva I. V. (2016, 2016)
Title screen